Water quality in streams and in points along the Parnaíba River, Floriano city, Brazil: abiotic factors, ecological risk and implications for environmental management - Lima, Rogério Nora; Lacerda, Ana Flavia de Sousa; Lima, Ricardo Araujo (ANAP Brazil, 2025)
ABSTRACT Objective - We wanted to analyze the water quality in urban streams and the Parnaíba River to characterize the effects of urban impact on abiotic variables and their ecological implications. Methodology - The study adopted a comparative and seasonal field methodology. Samples from 16 collection points (springs, mouths, and points upstream and downstream of the Parnaíba River) were analyzed over two years during two seasonal periods (dry and rainy). The analyzed variables included physico-chemical parameters (temperature, DO, pH, conductivity, turbidity, nutrients, and suspended solids). Originality/Relevance - The research addresses the gap in studies on the degradation of aquatic ecosystems in smaller cities in the Brazilian Northeast. Its relevance lies in documenting and validating, within the local context of Floriano-PI, the "Urban Stream Syndrome," a phenomenon widely reported in large urban centers, providing concrete data on the impacts of urbanization in semi-arid regions. Results - The results indicated a spatial gradient of degradation, with springs presenting better conditions (high DO, low nutrients and turbidity) and mouths exhibiting a high degree of pollution (NH₄⁺ > 2 mg/L, DO < 3 mg/L, turbidity > 150 NTU). The rainy season led to partial dilution of pollutants but without full recovery of water quality. Theoretical/Methodological Contributions - The study reinforces and applies the theoretical concept of "Urban Stream Syndrome". Methodologically, it demonstrates the effectiveness of a gradient approach (spring-mouth) combined with seasonal monitoring to accurately diagnose the impact of urbanization on watercourses. Social and Environmental Contributions - The study provides critical scientific evidence for public management, identifying urban streams as significant sources of degradation for the Parnaíba River. Its conclusions form a basis for demanding urgent public policies on basic sanitation, restoration of riparian forests, and the implementation of a continuous water quality monitoring program, aiming for environmental and public health.